2013
DOI: 10.1111/cpr.12041
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption in T‐47D cells immobilized in alginate

Abstract: The experimental set-up presented here may be varied in multiple ways by changing the cell-gel construct 3-D microenvironment, easily allowing investigation of a variety of factors on cell respiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 57 publications
4
5
0
Order By: Relevance
“…The increased number of data points, however, had minimal impact on R 2 values of linear regressions. As described previously, there was no significant fall in viability during the first 24 h in biostructures cultured under similar conditions , a finding we have also confirmed for several matrices and other types of cells (unpublished data).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The increased number of data points, however, had minimal impact on R 2 values of linear regressions. As described previously, there was no significant fall in viability during the first 24 h in biostructures cultured under similar conditions , a finding we have also confirmed for several matrices and other types of cells (unpublished data).…”
Section: Resultssupporting
confidence: 89%
“…N 0 denotes the number of cells originally added to the gel as estimated by counting samples of cell suspension in five plots of two separate Bürker chambers, and V gel is the volume of hydrogel used. This procedure was described in greater detail in our previous work .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have here studied several parameters influencing gelling kinetics and elasticity in particular. We have earlier found that the gel system allows conveniently entrapping cells in a 3D environment while preserving a high degree of viability, and that it was useful in a model system for the determination of cell respiration in this respect [ 34 , 35 ]. It has also been useful in constructs for cartilage regeneration and a formulation is currently undergoing clinical trials as a treatment for dilated cardiomyopathy [ 36 - 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the open-pore scaffold structure was sufficiently preserved by the alginate hydrogel and the EMD. Larsen et al 24 recently demonstrated the impact of the distance between cells immobilized in alginate to the cell medium interface in terms of oxygen diffusion. The findings from this study suggested that the distance between the immobilized cells to the cell medium interface was small enough to maintain viability.…”
Section: Discussionmentioning
confidence: 99%